Education under siege : the conservative, liberal and radical debate over schooling - Aronowitz, Stanley (Routledge, 1987)
Public spending on education is under attack. In this challenging book Aronowitz and Giroux examine the thinking behind that attack, in the USA and in other industrialized countries.